CHATBOT DESIGN USING ARTIFICIAL INTELLIGENCE WITH NATURAL LANGUAGE PROCESSING TO INCREASE CUSTOMER SATISFACTION AT MSME LEVEL - Khoeronsyah, Aria; Yuditama, Mohammad Rangga; Nurzaman, Muhammad Iqbal; Lesmana, Muhammad Ilham Surya; Fathurahman, Thaariq Muhammad; Rosita, Ai (CENTRAL ASIA AND THE CAUCASUS, 2022)
Customer satisfaction is a must, that has to be given by the merchant to the buyer in every transaction, therefore customer satisfaction must be maintained to retain customers in order to continue to gain their trust and loyalty to the goods and services offered. At this time, customer service is always used as a benchmark for customer satisfaction to understand and get information about the products and services offered by the merchant. However, there is a problem where merchants find it difficult to be able to present information about the products and services offer to the customer, for example if the merchant needs to respond and serve every message that comes in from various different platforms, the merchant will find it difficult and overwhelmed the transaction process that currently happens. This of course will result in customers trust and loyalty and reduce customer satisfaction with the services provided by the merchant. Therefore, comes up the idea of designing a chatbot system using artificial intelligence with natural language processing method that will be used to increase customer satisfaction and simplify deployment process usiing Application Programming Interface integration for the merchant.